Perancangan Sistem Pembayaran SPP Pada SMK Islam Iqro Pasar Kemis - Yuni Roza; Nurlaila Suci Rahayu Rais; Aditya Risdiarto Jati (UNIVERSITAS RAHARJA, 2020)
Islamic Vocational School Iqro Pasar kemis has the vision, mission and goals of graduates who have faith, piety and morality as well as competent in mastery of science and technology. But now Islamic vocational high school Iqro Pasar Kemis still use conventional way in conducting SPP transactions that is by noting the payment card and payment data manually recorded on the book. This causes the payment process to take a long time and a large errorrate, but it also inhibits the speed of data access and information delivery to be too late. With the existing problems then the researchers propose the design of payment systems to facilitate the process of payment of SPP. The research method used is SWOT analysis, for design method using Unified Modeling Language (UML), and system testing method using Blackbox Testing. This research is expected to provide easiness in the implementation of school fee payment activities as well as easiness in the delivery of school fee payment information to students and parents of students.